Does cannabis use substitute for opioids?: a preliminary exploratory survey in opioid maintenance patients - Bekier, Nina Kim; Frischknecht, Ulrich; Eidenmüller, Katharina; Grimm, Franz; Bach, Patrick; Stenger, Manuel; Kiefer, Falk; Hermann, Derik (European archives of psychiatry and clinical neuroscience, 2024)
Various studies showed that people with substance use disorder use cannabis to reduce withdrawal or dose of their main drug. Using a questionnaire about their cannabis use, 118 participants in an opioid maintenance treatment (OMT) in Germany were examined regarding this strategy. 60% reported to use cannabis. Of those, 72% were using cannabis in the suggested way. Cannabis was used to substitute for, e.g., heroin (44.8%) and benzodiazepines (16.4%). We also asked for an estimation of how good cannabis was able to substitute for several substances (in German school grades (1 till 6)); heroin average grade: 2.6 ± 1.49. Besides that we asked about the idea of cannabis as “self-medication”, e.g., to reduce pain (47%) and about negative consequences from cannabis use. Our results suggest to consider the use of cannabis by patients in OMT rather as a harm reduction strategy to reduce the intake of more dangerous drugs.
Online veröffentlicht: 19. März 2024
Gesehen am 03.12.2024